Knowing the adversary : leaders, intelligence, and assessment of intentions in international relations - Yarhi-Milo, Keren, 1978- (Princeton, New Jersey : Princeton University Press, 2014)
" States are more likely to engage in risky and destabilizing actions such as military buildups and preemptive strikes if they believe their adversaries pose a tangible threat. Yet despite the crucial importance of this issue, we don't know enough about how states and their leaders draw inferences about their adversaries' long-term intentions. Knowing the Adversary draws on a wealth of historical archival evidence to shed new light on how world leaders and intelligence organizations actually make these assessments. Keren Yarhi-Milo examines three cases: Britain's assessments of Nazi Germany's intentions in the 1930s, America's assessments of the Soviet Union's intentions during the Carter administration, and the Reagan administration's assessments of Soviet intentions near the end of the Cold War. She advances a new theoretical framework--called selective attention--that emphasizes organizational dynamics, personal diplomatic interactions, and cognitive and affective factors. Yarhi-Milo finds that decision makers don't pay as much attention to those aspects of state behavior that major theories of international politics claim they do. Instead, they tend to determine the intentions of adversaries on the basis of preexisting beliefs, theories, and personal impressions. Yarhi-Milo also shows how intelligence organizations rely on very different indicators than decision makers, focusing more on changes in the military capabilities of adversaries. Knowing the Adversary provides a clearer picture of the historical validity of existing theories, and broadens our understanding of the important role that diplomacy plays in international security. "--
Theories of intentions and the problem of attention -- Indicators of Nazi Germany's intentions and the coming of World War II, 1934-39 -- British decision makers' perceptions of Nazi Germany's intentions -- The British intelligence community's assessments of Nazi Germany's intentions -- The Carter era and the collapse of detente, 1977-80 -- US decision makers' perceptions of Soviet intentions : the collapse of detente -- The US intelligence community's assessments of Soviet intentions : the collapse of detente -- Indicators of Soviet intentions and the end of the Cold War, 1985-88 -- US decision makers' perceptions of Soviet intentions : the end of the Cold War -- The US intelligence community's assessments of Soviet intentions : the end of the Cold War -- Summary and implications.
Includes bibliographical references (pages 259-344) and index.
Keywords: Intelligence service; International relations; World politics -- 20th century; Detente; POLITICAL SCIENCE / International Relations / General; HISTORY / Modern / 20th Century; Great Britain -- Foreign relations -- 1936-1945.; Great Britain -- Foreign relations -- Germany; Germany -- Foreign relations -- Great Britain; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States